2019
DOI: 10.31220/osf.io/gz39p
|View full text |Cite
|
Sign up to set email alerts
|

Improving the oxidative stability of pork by antioxidant type phytonutrients.

Abstract: The objective of this study was to determine the influence of supplementations with 3.5 or 7.5 mg dihydroquercetin (experimental groups D1 and D2) or with 0.255 or 0.545 g dry distilled rose petals (experimental groups R1 and R2)/kg/d added as to pig's combined feed on the parameters of lipolysis expressed by acid value; lipid hydroperoxides expressed by peroxide value, lipid oxidation secondary products expressed by 2-tiobarbituric acid reactive substances (TBARS), pH and L*, a*, b* colour characteristics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(11 reference statements)
0
8
0
2
Order By: Relevance
“…Although some synthesis additives are effective, their potential toxicity for the human body is being considered. Recently, some relevant studies have reported that the utilization of natural antioxidants may be the alternative approach to protect food quality and safety (Mahajan et al., 2016; Vlahova‐Vangelova et al., 2020; Yu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although some synthesis additives are effective, their potential toxicity for the human body is being considered. Recently, some relevant studies have reported that the utilization of natural antioxidants may be the alternative approach to protect food quality and safety (Mahajan et al., 2016; Vlahova‐Vangelova et al., 2020; Yu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Positive results were obtained with the use of DHQ in the raising of broilers, including in conditions of high temperature [9], as well as in the raising of pigs with higher resistance to pre-slaughter stress [10].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were kept in the physiological yard of the L.K. Ernst Federal Science Center for Animal Husbandry (VIZh) from May 21 to September 28, 2019. Animals in all groups were kept under the same conditions (temperature, humidity and light regimes, the gas composition of the air inside the building), which corresponded to the zoohygienic norms in all groups.…”
Section: Materials and Methodologymentioning
confidence: 99%